Varian efikasi penularan tungro oleh koloni-koloni wereng hijau Nephotettix virescens distant - I Nyoman Widiarta; D. Kusdiaman; Sri S. Siwi; A. Hasanuddin (Jurnal Entomologi Indonesia, 2004)
Green leafhopper-resistant variety is one of rice tungro virus disease control measure. Green leafhopper (GLH), Nephotettix virescens is the most efficient vector of tungro. Among 7 sources of resistant gene to GLH 4 genes have been employed to breed resistant variety. Efficiency variant of GLH as indicated by their efficiency to transfer tungro virus was identified by inoculation test. GLH colonies were collected from tungro endemic areas in Java, Bali, West Nusa and South Sulawesi. Efficiency variant of GLH colony was characterized by their ability to transfer tungro virus to GLH-resistant variety with various source of resistant genes. Sources of tungro inoculum were obtained in Bogor. The results of the test showed that there was a variation in the ability of GLH colonies to tranfer tungro to various GLH-resistant variety, thus indicate there was a variant in GLH colony. The ability of GLH colonies to transfer virus ranked from high to low, were West Nusa Tenggara, Bali, East Java , South Sulawesi, D.I. Yogyakarta, West Java and Central Java. On the other hand GLH-resistant variety ranked from resistant to susceptible were varieties with resistant genes group glh4, Glh6, Glh1 and Glh5. Five variants colonies of GLH were successfully identified which named as colony 0050, 0000, 1050, 1650 and 1654. Biotype 0000 has the lowest ability to transfer virus but biotype 1654 efficiently transfer virus to all of GLH-resistant variety groups.